2003
DOI: 10.1161/01.cir.0000066912.58385.de
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation β-Blockers Stimulate Nitric Oxide Release From Endothelial Cells Through ATP Efflux

Abstract: Background-Nebivolol and carvedilol are third-generation ␤-adrenoreceptor antagonists, which unlike classic ␤-blockers, have additional endothelium-dependent vasodilating properties specifically related to microcirculation by a molecular mechanism that still remains unclear. We hypothesized that nebivolol and carvedilol stimulate NO release from microvascular endothelial cells by extracellular ATP, which is a well-established potent autocrine and paracrine signaling factor modulating a variety of cellular func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(160 citation statements)
references
References 21 publications
4
150
0
6
Order By: Relevance
“…Intriguingly, ␤-blockers with vasodilating properties, such as nebivolol and carvedilol, have also been reported to augment NO release from endothelial cells. 10 Recent studies in our laboratory demonstrated that celiprolol, a selective ␤ 1 -blocker with vasodilating properties, increased NO production in canine myocardial ischemia, 11 and we also reported that inhibition of eNOS can induce myocardial hypertrophy in rats. 12 However, very few studies were designed to explore the relation between eNOS signaling pathway and the inhibitory effect of ␤-blockers on cardiac remodeling.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Intriguingly, ␤-blockers with vasodilating properties, such as nebivolol and carvedilol, have also been reported to augment NO release from endothelial cells. 10 Recent studies in our laboratory demonstrated that celiprolol, a selective ␤ 1 -blocker with vasodilating properties, increased NO production in canine myocardial ischemia, 11 and we also reported that inhibition of eNOS can induce myocardial hypertrophy in rats. 12 However, very few studies were designed to explore the relation between eNOS signaling pathway and the inhibitory effect of ␤-blockers on cardiac remodeling.…”
mentioning
confidence: 59%
“…31 The mechanisms for the linkage of ␤ 1 -blockade to eNOS upregulation have been clarified by other investigators. Kalinowski et al 10 demonstrated that some ␤-blockers augment NO production via activation of ATP efflux, with consequent stimulation of P 2 Y purinoceptor. Celiprolol was also reported to activate eNOS through the PI3K-Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Tubular sodium transport systems are more sensitive to diadenosine tetraphosphate (Ap 4 A) than systems involved in glomerular filtration rates [167]. β-Blockers induce relaxation of the glomerular microvasculature by releasing ATP, which acts via P2Y receptors on endothelial cells to produce NO, resulting in vasodilation [180]. Connexin (Cx) 40 hemichannels and extracellular ATP are the key molecular elements of the glomerular endothelial calcium wave [371].…”
Section: Glomerulus and The Renal Vasculaturementioning
confidence: 99%
“…Third-generation ␤-blockers like carvedilol and nebivolol may enhance NO release in EC, increase vascular glutathione content, inhibit ROS formation, and reduce lipid peroxidation. 39 Several calcium channel blockers were shown to inhibit oxidation of LDL and other lipids in animals and humans. For example, nifedipine increases NO bioavailability by decreased ROS formation in EC and enhances MnSOD expression in VSMC.…”
Section: Drugsmentioning
confidence: 99%